Molecular fingerprinting methods for the discrimination between C-albicans and C-dubliniensis - Neppelenbroek, K. H.; Campanha, N. H.; Spolidório, Denise Madalena Palomari [UNESP]; Spolidório, Luis Carlos [UNESP]; Seo, R. S.; Pavarina, Ana Claudia [UNESP] (Blackwell Publishing, 2006)
Opportunistic fungal pathogens are becoming increasingly important causes of both community-acquired and nosocomial infections. The most important fungal pathogens are yeast species belonging to the genus Candida. These species show differences in levels of resistance to antifungal agents and mortality. Consequently, it is important to correctly identify the causative organism to the species level. Identification of Candida dubliniensis in particular remains problematic because of the high degree of phenotypic similarity between this species and Candida albicans. However, as the differences between both are most pronounced at the genetic level, several studies have been conducted in order to provide a specific and rapid identification fingerprinting molecular test. In most candidal infectious, no single DNA fingerprinting technique has evolved as a dominant method, and each method has its advantages, disadvantages and limitations. Moreover, the current challenge of these techniques is to compile standardized patterns in a database for interlaboratory use and future reference. This review provides an overview of most common molecular fingerprinting techniques currently available for discrimination of C. albicans and C. dubliniensis.
Keywords: candidiasis; oral; Candida; Candida albicans; pathology; isolation & purification; Candida dubliniensis